A Conceptual Framework for Gamified Learning Management System for LINUS Students - Syadiah Nor Wan Shamsuddin; Muhammad Faisal Selman; Ismahafezi Ismail; Maizan Mat Amin; Norkhairani Abdul Rawi (Institute of Advanced Engineering and Science, 2018)
Gamification is a term that refers to the use of game elements in non-game contexts. Gamification in education is emerging as an effective tool to motivate and engage learners in a variety of tasks. LINUS program is intended to ensure that all students from standard one are able to master the basics of reading, writing and counting at the end of standard three. Gamification will help as a learning tool to assist with the learning process for those who have difficulty in learning, unlike normal students. Therefore, the aim of this paper is to propose a framework of Gamified Learning Management System for Linus students. This framework consists of mechanisms of gamification elements, multimedia elements and learning theory that construct gamified learning management system.